IMPLEMENTASI PEMIKIRAN HAMZAH FANSURI DALAM PENDIDIKAN KARAKTER BERBASIS NILAI SPIRITUAL ISLAM DI SMA NURUL ILMI : PENDAHULUAN, METODOLOGI, HASIL, DISKUSI, KESIMPULAN - Juli Kustanto; Lia Laili Rosadah; Muhammad Fauzi; Abu Mansur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of Hamzah Fansuri’s thoughts in character education based on Islamic Spiritual Values at SMA Nurul Ilmi. Hamzah Fansuri, a prominent Malay Sufi scholar, emphasized the cultivation of noble character, sincerity, simplicity, and awareness of Islamic Spiritual Values as the foundation of social life. This research employs a descriptive qualitative method, with data collected through in-depth interviews with teachers and students, observations of Islamic Religious Education learning processes, and documentation of extracurricular activities oriented toward character strengthening. The findings reveal that Hamzah Fansuri’s values have been implemented through classroom learning, character guidance, and students’ daily practices. Values such as moral responsibility, patience, and social concern are reflected in students’ interactions and their application of Islamic teachings in everyday life. Furthermore, the integration of Sufi teachings encourages students to develop a deep awareness of Islamic Spiritual Values and to strengthen their character based on Islamic ethics. This study concludes that Hamzah Fansuri’s ideas can serve as a strategic foundation for developing character education based on Islamic Spiritual Values in secondary schools, particularly in shaping students who possess noble character, responsibility, and profound spiritual awareness.